Periodo crítico para el control de especies arvenses en el cultivo de maní (Arachis hypogaea L.) en el Cantón Celica - Provincia de Loja - Enríquez Viteri, María Belén (2023)
Peanut (Arachis hypogaea L.) is considered the sixth oilseed and economic crop worldwide, its importance lies in its nutritional value in the chain and food safety, it contains essential minerals and vitamins for human and animal health. The mature seeds are used as a high-protein food crop for people. One of the main factors that limits the production of this crop is the interference of weeds, because it directly and indirectly affects its production, competing for nutrients, water and radiation that, when scarce, compromise the development of the crop. The objective of this research was to identify the critical period for the control of weed species in the cultivation of peanuts (Arachis hypogaea L.) in the Celica Canton - Loja Province. The trial was established in the Quiara neighborhood located in the Celica Canton, using a plot design divided completely at random made up of 2 main plots, 8 subplots and 3 repetitions with a total of 48 experimental units, which consisted of 8 periods of interference of weeds and 8 periods without weed interference, where the evaluation of coverage, biomass and density of weeds was carried out; on the other hand, in the peanut crop, the final yield of the grain and its components was evaluated; The weeds that predominated in the crop were the Asteraceae with a percentage of 44% with respect to the other families; As for the yield, the number of grains generated the affectation of the yield due to the interference of weeds that reduced from 261 to 90 grains/plant and grew from 89 to 279 grains/plant in the periods without weeds. The critical period of weed interference was determined between 12 and 76 days after emergence (DDE), therefore the crop must remain free of weeds during the phenological stages from the appearance of the first pair of true leaves until development and filling. of the pods, in order to avoid yield losses greater than 10%. Keywords: Critical period, interference, weeds, yield.